Optical quantum computation: information processing using discrete- and continuous- variable states of light (2009)
Optical quantum computing uses measurement-based quantum computing schemes, with photons as physical qubits in the discrete case; it also takes advantage of the storage power of information available in the quadratures of the electromagnetic field that allows computation in a continuous-variable setting of quants, or units of analogic information. For the first case, the main physical architecture for computation is based on a proposal by Knill, Laflammeand Milburn, the KLM architecture. In the continuous case, the process of encoding changes substantially, as we are not working with qubits anymore; the process of computation changes respectively by redefining the set of gates as a set of operations over the continuous states of the optical quadratures. We will present an overview of the field of optical quantum computing both in the discrete case, focusing in the KLM protocol of computation, and in the continuous setting, which enables the implementation of some quantum algorithms in amore natural way by means of the continuous quantum Fourier transform. Exploiting the advantages of both schemes, we shall describe a form of hybrid computation that involves optical qubits and quants in the processing of information and apply it in the construction of the Deutsch-Jozsa algorithm.